The Validity of Issuing a Family Card for Unregistered Marriage Status: Keabsahan Penerbitan Kartu Keluarga Berstatus Kawin Belum Tercatat - Khasanah, Sofiyatul (Annual Review of Legal Studies, 2024)
Registering a marriage that has taken with an institution that has the right provide legelization for marriage registration, is a condition for validity of the marriage. registering a marriage is proof that a marriage has occurred and results in the issuing a family. This family card is one of the piece of evidence in administering the child in the future. Then what about couples who have married but not have not yet registerered their marriage? The government has innovated for couples who want to issue a family card but are still hampered by not having a marriage certificate, namely by providing a special identification card in the form of a Statement of Absolute Resposibility (SPTJM). With this special sign, couples who have not registered their marriage can apply for a family card. The purpose of the writing is to find out the validity of issuing unregistered cards and what the impct is on childern born from unregistered marriage. In order to find the results of this research, the type of researcher took was normative legal research. Normative legal research aims to enable researchers to solve problem by using various library materials that are appropriate to the research object. With this research, the reachers conclude that making a family card with nregistered marital status is valid or legal. By using SPTJM where SPTJM has been regulated in existinng legislation in Indonesia. The Impact for childern born to unregistered married couples is the child will lose the right they have, in the form of posiyion and status of the child , right to inheritance, and right to identy.